2020
DOI: 10.1049/el.2019.3752
|View full text |Cite
|
Sign up to set email alerts
|

Very‐large‐scale integration implementation of a convolutional neural network accelerator for abnormal heartbeat detection

Abstract: In this study, a very-large-scale integration implementation of a convolutional neural network (CNN) inference for abnormal heartbeat detection was proposed. Four-lead electrocardiogram signals were used to detect abnormal heartbeat conditions, such as premature ventricular complex. 1D CNNs and fully connected layers were utilised in the proposed chip to achieve high-speed, small-area, and high-accuracy arrhythmia detection. The proposed chip was implemented using a 90-nm complementary metal-oxide-semiconducto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…A summary of this work specification and other previous designs are illustrated in Table 2. This work achieves better classification accuracy, adapting gated recurrent neural network than other works [2–5 ], and lower power consumption is achieved by using asynchronous spike‐driven logic.…”
Section: Results and Implementationmentioning
confidence: 93%
See 1 more Smart Citation
“…A summary of this work specification and other previous designs are illustrated in Table 2. This work achieves better classification accuracy, adapting gated recurrent neural network than other works [2–5 ], and lower power consumption is achieved by using asynchronous spike‐driven logic.…”
Section: Results and Implementationmentioning
confidence: 93%
“…To achieve a target to automate arrhythmia monitoring, several ECG-based detections have been reported by using artificial intelligence processors [2][3][4][5]. In [2], a very-large-scale integration implementation was proposed using a convolutional neural network (CNN) layer and a fully connected neural network (FNN) layer inference models for abnormal heartbeat detection. This chip utilised a one-dimensional (1D) CNN layer and a fully connected layer to process the ECG signal as a 2D image, achieving 95.14% in detecting arrhythmia.…”
mentioning
confidence: 99%
“…In general, our proposed work offers several advantages over the previous works. First, the proposed work achieves high classification accuracy while occupying a relatively smaller area, making it more compact compared to the previous works as proposed by [16] and [17]. In addition, the proposed DSNN circuit consumes only 0.75mW of power, which is significantly lower than both circuits as proposed by [16] and [17].…”
Section: Introductionmentioning
confidence: 93%
“…As a result, once a deep learning model is trained, it can be used to classify ECG signals into a number of arrhythmic events. In such aspects of applications, VLSI implementations of CNNbased techniques for abnormal heartbeat detection were proposed in previous studies in literature [16]- [17]. The results obtained from these works have shown that the hardware realization of CNN for ECG heartbeat classification may achieve high speed, small area, and low power dissipation with a high detection rate, thus improving early detection and timely treatment of cardiac disorders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation